Antibiotic-Loaded Cement in Orthopedic Surgery: A Review. (7th August 2011) - Bistolfi, Alessandro; Massazza, Giuseppe; Verné, Enrica; Massè, Alessandro; Deledda, Davide; Ferraris, Sara; Miola, Marta; Galetto, Fabrizio; Crova, Maurizio
Abstract : Infections in orthopaedic surgery are a serious issue. Antibiotic-loaded bone cement was developed for the treatment of infected joint arthroplasties and for prophylaxes in total joint replacement in selected cases. Despite the widespread use of the antibiotic-loaded bone cement in orthopedics, many issues are still unclear or controversial: bacterial adhesion and antibiotic resistance, modification of mechanical properties which follows the addition of the antibiotic, factors influencing the release of the antibiotic from the cement and the role of the surface, the method for mixing the cement and the antibiotic, the choice and the effectiveness of the antibiotic, the combination of two or more antibiotics, and the toxicity. This review discusses all these topics, focusing on properties, merits, and defects of the antibiotic loaded cement. The final objective is to provide the orthopaedic surgeons clear and concise information for the correct choice of cement in their clinical practice.